2021
DOI: 10.1093/hmg/ddab042
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses of scRNA-seq and scATAC-seq reveal CXCL14 as a key regulator of lymph node metastasis in breast cancer

Abstract: The potentially different genetics and epigenetics in the primary tumors and metastases affect the efficacy of treatment in breast cancer patients. Nevertheless, the cellular and molecular mechanisms of breast cancer lymph node metastasis still remain elusive. Here, we employed single-cell RNA sequencing (scRNA-seq) to acquire the transcriptomic profiles of individual cells from primary tumours, negative, and positive lymph nodes. We also performed a single-cell assay for transposase-accessible chromatin (ATAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…β2-microglobulin, which is encoded by B2M, is an essential component of MHC class I. Previous studies on pancreatic ductal adenocarcinoma, colorectal cancer, and melanoma showed that loss of B2M was an indicator of poor dismal prognosis, including lymph node metastasis, recurrence, and therapy resistance [ 11 , 24 , 25 ]. The high expression of B2M and MHC class I in metastases enabled a better chance for immune recognition and attack.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…β2-microglobulin, which is encoded by B2M, is an essential component of MHC class I. Previous studies on pancreatic ductal adenocarcinoma, colorectal cancer, and melanoma showed that loss of B2M was an indicator of poor dismal prognosis, including lymph node metastasis, recurrence, and therapy resistance [ 11 , 24 , 25 ]. The high expression of B2M and MHC class I in metastases enabled a better chance for immune recognition and attack.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported gene expression characteristics of breast cancer lymph node metastasis [ 2 , 5 , 7 ]. Across multiple studies conducted over the years, including a tentative exploration of chromatin accessibility during lymph node metastasis derived from one breast cancer patient [ 24 ], no single best delineation has been identified to understand the transcriptome diversity of metastatic breast cancer at a single-cell level, nor were comparisons made between primary tumors and lymph node metastasis. The theme of self-renewing cancer cells, epithelial-mesenchymal transition, and tumor-immune escape seem to be recapitulated in research on many malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, the chemokine receptors CXCR4 and CCR7 have been involved in the process of the lymph node metastatization and the expression of their ligands CXCL12 and CCL21 by lymphatic endothelial cells attract tumours cells into lymphatic vessels [52,91]. Recently, Xu and colleagues [92] identified and validated a cell subpopulation of breast cancer cells with a high expression level of CXCL14 in the positive lymph nodes of breast cancer patients. The CXCL14 expression was significantly higher in breast cancer patients with lymph node metastasis, suggesting this protein as a new prognostic marker for lymphatic metastasis [92].…”
Section: Molecular Insights In Breast Lymphaticsmentioning
confidence: 99%
“…Moreover, the heterogeneity between the primary tumor and metastases in lymph nodes was assessed using scRNA-seq, and a novel cell subpopulation called CXCL14 cancer cells was identified in the positive lymph nodes of breast cancer patients. ATAC-seq of the positive and negative lymph node samples further revealed the chromatin accessibility profile and identified potential TFs related to CXCL14 cancer cells, including ZNF467, bZIP, EBF1, and PIT1, in the lymph node metastases of breast cancer ( 88 ).…”
Section: Single-cell Sequencing In Cancer: Lessons Learnedmentioning
confidence: 99%